Leprosy among children in an area without primary health care coverage in Caratateua Island, Brazilian Amazon - Costa, Izabelle Laissa Viana; da Costa, Patrícia Fagundes; da Silva, Sâmela Miranda; Gobbo, Angélica Rita; Pinto, Pablo Diego do Carmo; Spencer, John Stewart; da Silva, Moises Batista; Salgado, Claudio Guedes (Frontiers in Medicine, 2023)
Introduction The detection of leprosy in children is an important epidemiological marker of the disease, indicating the community’s early exposure to Mycobacterium leprae and active transmission of the infection. Methods In order to detect new cases among children by combining clinical evaluation and laboratory tests, we conducted an active case finding among individuals under 15 years old on Caratateua Island, located in the city of Belém, in the Pará state, an endemic region in the Amazon. Dermato-neurological examination, collection of 5 mL of peripheral blood for IgM anti-PGL-I antibody titration, and intradermal scraping for bacilloscopy and amplification of the specific RLEP region by qPCR were performed. Results Out of the 56 examined children, 28/56 (50%) new cases were identified. At the time of evaluation, 38/56 (67.8%) children presented one or more clinical alterations. Seropositivity was detected in 7/27 (25.9%) new cases and 5/24 (20.8%) undiagnosed children. DNA amplification of Mycobacterium leprae was observed in 23/28 (82.1%) of new cases and in 5/26 (19.2%) of non-cases. Out of the total cases, 11/28 (39.2%) were exclusively diagnosed by clinical evaluation performed during the active case finding. Seventeen new cases (60.8%) were detected considering the clinical alterations found in addition to positive results for qPCR. In this group, 3/17 (17.6%) qPCR-positive children presented significant clinical changes 5.5 months after the first evaluation. Discussion Our research detected a number of cases 5.6 times higher compared to the total number of pediatric cases recorded throughout the year 2021 in the municipality of Belém, which shows a critical scenario of underdiagnosing of leprosy among children under 15 years old in the region. We propose the use of qPCR technique to identify new cases among children with oligosymptomatic or early disease in endemic areas, in addition to the training of Primary Health Care professionals and the implementation of the Family Health Strategy coverage in the visited area.